Cancer immunotherapy and immune-related response assessment: The role of radiologists in the new arena of cancer treatment. Issue 7 (July 2015) - Nishino, Mizuki; Tirumani, Sree H.; Ramaiya, Nikhil H.; Hodi, F. Stephen
Highlights: The successful clinical application of cancer immunotherapy has opened a new arena for the treatment of advanced cancers. Cancer immunotherapy is associated with a variety of important radiographic features in the assessments of tumor response and immune-related adverse events. The state-of-the art knowledge of immunotherapy and the related radiologic manifestations are essential for radiologists. Abstract: The recent advances in the clinical application of anti-cancer immunotherapeutic agents have opened a new arena for the treatment of advanced cancers. Cancer immunotherapy is associated with a variety of important radiographic features in the assessments of tumor response and immune-related adverse events, which calls for radiologists' awareness and in-depth knowledge on the topic. This article will provide the state-of-the art review and perspectives of cancer immunotherapy, including its molecular mechanisms, the strategies for immune-related response assessment on imaging and their pitfalls, and the emerging knowledge of radiologic manifestations of immune-related adverse events. The cutting edge clinical and radiologic investigations are presented to provide future directions.